DESCRIPTION OF EARLY DETECTION AND PREVENTION OF HYPERTENSION IN BLANG MONLUNG VILLAGE IN THE WORKING AREA OF LHOK KRUET HEALTH CENTER - Lensoni , Lensoni; Hidayah, Hidayah (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Hypertensive disease is one of the significant health problems, both in the world and in Indonesia. Hypertension, often referred to as the "silent killer," is a deadly disease that often shows no signs or symptoms as an early warning. Over time, uncontrolled blood pressure will increase and lead to decreased organ function. Hypertension is an abnormal increase in blood pressure that is the main cause of various cardiovascular diseases. This study aims to describe the efforts of early detection and prevention of hypertension in Blang Monlung Village, Lhok Kruet Health Center working area. The research method used is quantitative with descriptive design. The population in this study were 150 respondents, who were also used as samples using the total sampling technique. Data were collected through a questionnaire that included information regarding living habits, medical history, and preventive measures taken by respondents to control hypertension. The results of the study are expected to provide a clear picture of the level of awareness and preventive actions taken by the community in detecting and preventing hypertension. In addition, these results can also help the Lhok Kruet Health Center in designing more effective health programs to address the problem of hypertension in Blang Monlung Village. Thus, this study contributes to efforts to improve public health through targeted education and interventions.